RISK FACTORS AND FEATURES OF PREGNENCY, DELIVIRIES AND THE FETUS CONDITION IN HIV-INFECTED WOMEN - Оксана Николаевна Новикова; Екатерина Михайловна Швец (The Publishing House Medicine and Enlightenment, 2017)
The growing number of people infected with human immunodeficiency virus (HIV) in Russia nearly by 400 thousand during 2016 with women mostly infected makes the study of this issue relevant. Objective - to study the risk factors and features of a course of pregnancy, birth and the fetus condition in HIV-infected women. Materials and Methods. We conducted a retrospective case-control study that includes 180 women. The main group consisted of 90 HIV-positive pregnant women and their newborns, the control group - 90 pregnant women without symptoms of HIV infection and their newborn. Results. Sexually transmitted HIV occurred in 71 patients (79 %). The viral load of more than 1000 copies / ml was diagnosed in 30 % patients. Failure to receive antiretroviral therapy (ART) during pregnancy has been observed in 40 % patients. In the main group nicotine and drug dependence, chronic diseases are significantly more often observed. Among the complications of pregnancy vaginal dysbiosis, yeast vulvovaginitis, gestational edema, threatening abortion in the second trimester, abnormal fetal presentation are observed. The deliveries usually performed by the caesarean section were indicated by high viral load and the anomalies of labor activity. The frequency of episiotomy and perineal ruptures increased in spontaneous deliveries. Newborns of HIV-positive women more often have intrauterine growth retardation and higher overall morbidity. In addition, the lack of contact of the infected women with qualified specialists, late search for medical care, poor adherence to the treatment lead to the absence or inadequacy of ART that increases the risk of the vertical HIV transmission.